G Protein-Coupled Estrogen Receptor Protects From Angiotensin II-Induced Increases in Pulse Pressure and Oxidative Stress - Ogola, Benard O.; Zimmerman, Margaret A.; Sure, Venkata N.; Gentry, Kaylee M.; Duong, Jennifer L.; Clark, Gabrielle L.; Miller, Kristin S.; Katakam, Prasad V. G.; Lindsey, Sarah H. (Frontiers in Endocrinology, 2019)
Our previous work showed that the G protein-coupled estrogen receptor (GPER) is protective in the vasculature and kidneys during angiotensin (Ang) II-dependent hypertension by inhibiting oxidative stress. The goal of the current study was to assess the impact of GPER deletion on sex differences in Ang II-induced hypertension and oxidative stress. Male and female wildtype and GPER knockout mice were implanted with radiotelemetry probes for measurement of baseline blood pressure before infusion of Ang II (700 ng/kg/min) for two weeks. Mean arterial pressure was increased to the same extent in all groups, but female wildtype mice were protected from Ang II-induced increases in pulse pressure, aortic wall thickness, and Nox4 mRNA. In vitro studies using rat aortic smooth muscle cells found that pre-treatment with the GPER agonist G-1 inhibited Ang II-induced ROS and NADP/NADPH. Ang II increased while G-1 decreased Nox4 mRNA and protein. The effects of Ang II were blocked by losartan and Nox4 siRNA, while the effects of G-1 were inhibited by adenylyl cyclase inhibition and mimicked by phosphodiesterase inhibition. We conclude that during conditions of elevated Ang II, GPER via the cAMP pathway suppresses Nox4 transcription to limit ROS production and prevent arterial stiffening. Taken together with our previous work, this study provides insight into how acute estrogen signaling via GPER provides cardiovascular protection during Ang II hypertension and potentially other diseases characterized by increased oxidative stress.